Phenomena of Child Involvement in Literacy Practices in the Province of Yogyakarta Special Region: A Communication Study - Primadesi, Yona (Universitas Negeri Padang, 2022)
Literacy hegemony is currently formed by the cultural practices of the dominant social group, in this case, adult humans. The whole practice is seen from the eyes of adults as a form of the legitimacy of power. Since 2017 the phenomenon of children's involvement in literacy practices has increased. Even though children work together with adults in their operations, they are able to accommodate their needs well. This article tries to look at communication activities that occur in the phenomenon of children's involvement in literacy practices in the Province of the Special Region of Yogyakarta. The writing of this article is based on the theory of symbolic and sociocultural interaction with a constructivist approach. The research informants consisted of 5 elementary school children in the Special Region of Yogyakarta Province who had a consistent and measurable literacy trajectory and were involved in various literacy practices from 2017 to 2019. The results showed that communication activities in children involved in literacy practices partially begin early, intensely, and in a conducive communication environment. The presence of parents or adults around the child is decisive. Creating space for discussion and children's participation through play activities and text media forms interactions that help children's cognitive and affective development, encouraging children's involvement in literacy practices